Principles of electronic circuits - Burns, Stanley G. (PWS, 1997)
Electronic circuit fundamentals. Introduction to semiconductors. Semiconductor diodes and diode circuits. The bipolar junction transistor. The field-effect transistor. Basic analysis techniques. Biasing and stability. Small-signal midfrequency amplifier analysis. Frequency effects in small-signal amplifiers. Operational amplifier circuitry. Feedback. Operational amplifier examples. Integrated-circuit logic gates. Small digital subsystems. Semiconductor memories...